Aid Effectiveness—Opening the Black Box - Bourguignon, François; Sundberg, Mark (American Economic Review, 2007)
The empirical literature on aid effectiveness has yielded unclear and ambiguous results. This is not surprising given the heterogeneity of aid motives, the limitations of the tools of analysis, and the complex causality chain linking external aid to final outcomes. The causality chain has been largely ignored and as a consequence the relationship between aid and development has been mostly handled as a kind of 'black box'. Making further progress on aid effectiveness requires opening that box. This paper examines the causality chain linking aid flows to development outcomes. It argues that many of the questions that policy makers and economists would like to squeeze data into answering simply cannot be answered due to the complexity and ‘noise ’ along links in the chain, and hence the problem of attribution. It then examines what is known about aid effectiveness along different links in the causality chain. Finally, it turns to recent trends in the way aid is delivered and the new model that appears to be emerging. I. The ‘causality chain’: aid, effectiveness and results The debates around the impact of aid on development have typically aggregated